Application of Lean Manufacturing Using Kaizen Analysis: A Case Study - Surya, Amit; Kumar, Rakesh; Trehan, Rajeev (Journal of Graphic Era University, 2024)
Industrial production and operation have been completely transformed by lean methods made possible by lean management (LM) technologies in the industry. This paper investigates industry practices regarding the application of lean tools in the manufacturing sector. For the purpose of gathering data, a questionnaire survey was distributed among the manufacturing professionals in the organization where lean manufacturing has already been adopted. The purpose of the study is to highlight the perceived level of their contribution to operational performance. In order to access operational performance, the study uses lean tools such as root-cause analysis, kaizen hypothesis, and evaluation of kaizen hypothesis, as well as before and after comparison. The study confirms that widespread adoption of lean practices results in a decrease in setup time from 28 minutes to 6 minutes, an increase in productivity by 50 components per month, a reduction in average wheel damage, and average components being reworked.